2022
DOI: 10.14444/8321
|View full text |Cite
|
Sign up to set email alerts
|

Upper Cervical Spine Injuries: Profile and Management of 120 Cases

Abstract: Objectives: To identify the profile and management of patients with upper cervical spine injury. Methods: Retrospective cohort study of patients with upper cervical spine injuries managed at Hospital da Restauração between 2014 and 2020.Results: It presents the profile of 145 injuries recorded by location and classification among the 120 patients, and the management performed. Men are more affected than women, almost half of the patients (42.5%) were aged 16 to 29 years. Neurological deficit was present in 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Since the result matrix was a series of complex numbers, their spectrum and phases were extracted from the signals. After that, the most common statistical characteristics in the literature were extracted through the following Matlab commands: average (1), standard deviation (2), root mean square (3), shape factor (4), peak value, signal to noise ratio crest factor (5), and signal to noise and distortion ratio (6).…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the result matrix was a series of complex numbers, their spectrum and phases were extracted from the signals. After that, the most common statistical characteristics in the literature were extracted through the following Matlab commands: average (1), standard deviation (2), root mean square (3), shape factor (4), peak value, signal to noise ratio crest factor (5), and signal to noise and distortion ratio (6).…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
“…The most common of these injuries are due to traffic accidents, violence, sports, or falls. Globally, the incidence ranges from 10.4 to 83 in developed countries, with 53.9% of these cases affecting the cervical spine [5]. Most people who suffer this type of injury are at a young and productive age [6]; therefore, when faced with this new disability, they also face significant economic losses due to the cost and duration of rehabilitation, as well as those caused by the disability itself.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical spinal cord injuries result in spinal cord paralysis [11], [12]. Studies have shown the success of implantable devices in treating Blindness, Degenerative Disease, Parkinson's Disease, Epilepsy and Alzheimer's.…”
Section: Incidencementioning
confidence: 99%